Aristotle’s Lost Symposium and On Drunkenness. The Content of The Extant Testimonies and Excerpts - Jaworska-Wołoszyn, Magdalena (Peitho. Examina Antiqua, 2016)
Ancient catalogues of Aristotle’s writings (Diogenes Laertius, Hesychius) mention Symposium in one book, but this does not seem to be a dialogue analogical to that of Plato. Aristotle raised the sympotical and wine-drinking issues differently, as Plutarchus, Macrobius, Philo of Alexandria, Ps. Julian, and first and foremost, Atheaneus relate in their works. In his The Sophists at Dinner, Atheaneus quotes Aristotle’s title Συμπόσιον only once, while the title Περὶ μέθης is cited six times. Some scholars and editors of Aristotle’s fragments combine both titles as belonging to one writing (Laurenti, Zanatta), while others (Gigon, Breitenberger) separate them as their identity is not confirmed by the sources. Irrespective of whether it was a dialogue, just one or two related works, the few extant testimonies and citations from Aristotle provide an interesting source of information concerning the then customs and drinking effects in Greek culture, which, however, should not be directly associated with contemporary drunkenness and alcoholism. Aristotle’s approach to wine-drinking and feasting was in fact investigative, natural, medical, and analogical to the arguments presented in the third book of Problemata, where the matters On the drinking of wine and drunkenness are touched upon.